Strengthening Teamwork in the Pancasila Student Profile (P5) Project: A Qualitative Study of Collaborative Learning Implementation - Ina Hasanah Hasanah; Wahab Wahab; Sugeng Listyo Prabowo (Universitas Nurul Jadid, 2026)
Educational reform increasingly emphasizes character development and collaborative learning as essential components of twenty-first-century education. Within this context, the Pancasila Student Profile Strengthening Project (P5) is a project-based learning initiative that integrates academic learning with character formation. This study aims to examine how teamwork is strengthened during the implementation of P5 and how collaborative practices contribute to the development of an effective and adaptive school environment. Employing a qualitative case study approach, data were collected through semi-structured interviews, field observations, and document analysis involving school leaders, teachers, and project implementation teams. The findings reveal that teamwork functioned as a central mechanism supporting successful program implementation through coordinated stages, including collaborative planning, stakeholder socialization, project execution, and reflective evaluation. Collective professional practices encouraged a shift from individual teaching routines toward shared responsibility, enabling teachers to integrate interdisciplinary learning and facilitate meaningful student participation. The study also found that project-based activities promoted students’ engagement, responsibility, creativity, and collaborative skills. However, challenges such as limited instructional time and the persistence of individual work habits remained evident. These results highlight that curriculum innovation becomes more sustainable when supported by organizational collaboration rather than relying solely on instructional change. The findings offer practical insights for strengthening collaborative school cultures to support long-term educational transformation.